Asia Rising A Handbook of History and International Relations in East, South and Southeast Asia - Sahashi, Ryo.; Matsuda, Yasuhiro; Aoyama, Waka.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open-access book offers a clear and thorough exploration of Asia's history from an international relations perspective. The book investigates key political, economic, and cultural forces defining Asia. It highlights the historical and current significance of the Indo-Pacific region, particularly shedding light on its strategic role in global geopolitics. Through detailed historical analyses, the authors guide readers toward a comprehensive understanding of Asia's complex international relations, from colonization and imperialism, through the Cold War, into decolonization and the wave of democratization in the region, to the rise of China, unpacking the various dimensions of regionalism in Asia. This book serves as a practical scholarly resource for advanced students, researchers, and lecturers interested in understanding the region's past and its implications for future geopolitical dynamics. It is relevant to historians focused on Asia and to international relations and political science scholars interested in the shift to an Asian world order, from past to present.
Chapter 1 Introduction: What is Asia? -- Chapter 2 Prosperity in Asia -- Chapter 3 Colonization and Imperialism East Asia and Imperialism -- Chapter 4 Japan$1 (Bs Expansion into Asia -- Chapter 5 Colonialism and War-torn Asia From the Concept of Postwar Order to the Cold War System.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Asia -- History; Imperialism; International relations; Asia -- Politics and government; Philosophy; Postcolonialism; Asian History; Imperialism and Colonialism; International Relations; Asian Politics; Postcolonial Philosophy